Perbedaan Adekuasi Hemodialisis pada Pasien Akses AV Shunt dan AV Femoral - Pranowo, Suko; Hartati, Ida; Kasron, Kasron (HB PRESS, 2024)
Adequacy of hemodialysis is the adequacy of the number of hemodialysis processes which is characterized by patients feeling better and comfortable. Hemodialysis access can be done with an Arterio-Venous (AV) shunt will increase blood flow rapidly. Another access to get central venous access can use the femoral AV. The use of hemodialysis access can affect adequacy. The purpose of this study was to determine differences in the adequacy of hemodialysis in patients with AV shunt and AV Femoral access. This research uses quantitative research with comparative descriptive method. Time approach using cross sectional. A sample of 32 people were divided into 2 groups, namely the AV shunt access group and the AV femoral access group. The sampling technique used a purposive sampling technique in accordance with the inclusion and exclusion criteria. Data analysis used independent t-test. The average urea level in hemodialysis patients with AV shunt access was 74.72% and AV femoral access was 67.05%.There was a significant difference in the adequacy of hemodialysis in patients with AV shunt and AV femoral access (pv = 0.013). Cilacap General Hospital is advised to improve its services by opening an AV shunt installation facility and providing education to Chronic Renal Failure (CRF) patients so that patients are motivated to install an AV shunt.